2014
DOI: 10.3389/fphys.2014.00435
|View full text |Cite
|
Sign up to set email alerts
|

Exploring susceptibility to atrial and ventricular arrhythmias resulting from remodeling of the passive electrical properties in the heart: a simulation approach

Abstract: Under diseased conditions, remodeling of the cardiac tissue properties (“passive properties”) takes place; these are aspects of electrophysiological behavior that are not associated with active ion transport across cell membranes. Remodeling of the passive electrophysiological properties most often results from structural remodeling, such as gap junction down-regulation and lateralization, fibrotic growth infiltrating the myocardium, or the development of an infarct scar. Such structural remodeling renders atr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 95 publications
0
27
0
Order By: Relevance
“…Notably, this research thrust has been paralleled by similar efforts to develop and utilize patient-specific models of ventricular arrhythmias that involve structural and fibrotic remodelling. 54,55 This includes studies aiming to estimate ablation targets for scar-related ventricular tachycardia 56 and stratify risk of lethal arrhythmias in post-myocardial infarction patients, including individuals for whom insertion of implantable defibrillators is clinically indicated 57 and (as discussed elsewhere in this supplement) those for whom it is not. 58 Furthermore, the field has now progressed to an exciting stage where computer modellers and clinicians are on the precipice of a truly thrilling collaboration that will involve the execution of catheter ablations in patients based on optimal treatment plans derived from pre-procedure simulations that take into account each individual's unique pattern of fibrotic structural remodelling.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, this research thrust has been paralleled by similar efforts to develop and utilize patient-specific models of ventricular arrhythmias that involve structural and fibrotic remodelling. 54,55 This includes studies aiming to estimate ablation targets for scar-related ventricular tachycardia 56 and stratify risk of lethal arrhythmias in post-myocardial infarction patients, including individuals for whom insertion of implantable defibrillators is clinically indicated 57 and (as discussed elsewhere in this supplement) those for whom it is not. 58 Furthermore, the field has now progressed to an exciting stage where computer modellers and clinicians are on the precipice of a truly thrilling collaboration that will involve the execution of catheter ablations in patients based on optimal treatment plans derived from pre-procedure simulations that take into account each individual's unique pattern of fibrotic structural remodelling.…”
Section: Discussionmentioning
confidence: 99%
“…In computer models, fibroblast-myocyte coupling has been represented using a fibrosis kinetic ionic model coupled to neighboring normal atrial myocytes. (59-61) In one of these studies conducted by the Trayanova group using the sophisticated biophysics-based cellular model for fibroblasts and patient-specific fibrotic distribution based on in-vivo DE-MRI suggested that the distribution of atrial fibrosis dictates where reentrant AF drivers are perpetuated. (59,60) These studies also showed that simulated reentrant activities were exacerbated with increased fibroblast-myocyte coupling and absent when fibrosis was made non-conductive.…”
Section: Recent Advances In Computer Modeling Of Af and Fibrosismentioning
confidence: 99%
“…(59-61) In one of these studies conducted by the Trayanova group using the sophisticated biophysics-based cellular model for fibroblasts and patient-specific fibrotic distribution based on in-vivo DE-MRI suggested that the distribution of atrial fibrosis dictates where reentrant AF drivers are perpetuated. (59,60) These studies also showed that simulated reentrant activities were exacerbated with increased fibroblast-myocyte coupling and absent when fibrosis was made non-conductive. Biophysics-based approaches that take into account fibroblast-myocyte coupling can reveal the role of this coupling in AF mechanism in-silico but the existence of fibroblast-myocyte coupling in human atria is still debated.…”
Section: Recent Advances In Computer Modeling Of Af and Fibrosismentioning
confidence: 99%
“…Tissue level studies can be extended to investigate anatomical abnormalities, reduced coupling, anisotropy and even pathological settings such as the infarct border zone and end-stage heart failure 45, 54, 111, 146 . Models are generally developed as follows: (1) Models of normal or diseased myocardium are developed based on experimental data sets.…”
Section: Cardiac Electrophysiological and Mechanical Modelsmentioning
confidence: 99%